2010
DOI: 10.2353/jmoldx.2010.090188
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sanger Sequencing, Pyrosequencing, and Melting Curve Analysis for the Detection of KRAS Mutations

Abstract: Mutations in codons 12 and 13 of the KRAS oncogene are relatively common in colorectal and lung adenocarcinomas. Recent data indicate that these mutations result in resistance to anti-epidermal growth factor receptor therapy. Therefore, we assessed Sanger sequencing, pyrosequencing, and melting curve analysis for the detection of KRAS codon 12/13 mutations in formalin-fixed paraffin-embedded samples, including 58 primary and 42 metastatic colorectal adenocarcinomas, 63 primary and 17 metastatic lung adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
360
3
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(393 citation statements)
references
References 16 publications
21
360
3
4
Order By: Relevance
“…A number of new technologies have also been applied to KRAS testing, such as high-resolution melting analysis and pyrosequencing. The latter has the advantage of higher sensitivity than regular dideoxysequencing [20].…”
Section: Discussionmentioning
confidence: 99%
“…A number of new technologies have also been applied to KRAS testing, such as high-resolution melting analysis and pyrosequencing. The latter has the advantage of higher sensitivity than regular dideoxysequencing [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the same single lesion can harbor more than one independent clone ( 2 , 57 , 58 ). These observations are particularly relevant when considering that previous studies mainly involved analysis of KRAS exon 2 mutations, and that the most commonly used techniques (Sanger sequencing) have a limit of detection of approximately 15% to 20% ( 59 ). Of interest, it has been shown that more sensitive approaches such as pyrosequencing or digital PCR can increase the detection of mutant RAS alleles, which in turn could translate into the detection of additional refractory patients ( 22 , 57 , 58 , 60 , 61 ).…”
Section: Other Suspectsmentioning
confidence: 99%
“…We elected not to Sanger confirm every additional variant despite this approach being the purported gold standard. More than half of our detected variants harbored VAFs <20%, and with published sensitivities of 15% to 20% for variant detection, 34 we reasoned Sanger confirmation was an insensitive method for confirmation. Unfortunately, comprehensive confirmatory sequencing was not practical because of cost and paucity of remaining sample material, highlighted by a discrepant KRAS p.G13C mutation that was not detected by SNaPshot analysis (NSCLC-4).…”
Section: Targeted Ngs For the Clinical Laboratorymentioning
confidence: 99%